Hiding from history : politics and public imagination - Steele, Meili, 1949- (Cornell University Press, 2005)
"In Hiding from History, Meili Steele challenges an assumption at the heart of current debates in political, literary, historical, and cultural theory: that it is impossible to reason through history. Steele believes that two influential schools of contemporary thought "hide from history": liberal philosophies of public reason as espoused by such figures as Jurgen Habermas, Martha Nussbaum, and John Rawls and structuralism/poststructuralism as practiced by Judith Butler, Hayden White, and Michel Foucault. For Steele, public reasoning cannot be easily divorced from either the historical imagination in general or the specific legacies that shape, and often haunt, political communities."--Jacket